Managing food industry waste : - Zall, Robert R. (Blackwell Pub., 2004)
In Managing Food Industry Waste: Common Sense Methods for Food Processors, waste management expert Robert Zall shares his philosophy and techniques for monitoring and accounting for food processing wastage. The text shows food processing managers how much of the waste now being generated can become a managed resource for producing economic credits. Drawing on his forty years of experience in managing waste, Zall explains how to identify the actual losses sent to drains and sewage treatment plants, how to pinpoint which unit processes generate these losses, and how to uncover hidden losses previously dismissed as “materials unaccounted for.” An extra feature of the book is a Self-Test covering waste treatment technology, ideal for students or new employees studying waste management. Also included is a Glossary of terms used in water and waste management. Managing Food Industry Waste is a highly readable management tool filled with invaluable waste management concepts and practical methods to implement them.